The Life of Johnny Reb : The Common Soldier of the Confederacy - Wiley, Bell Irvin, 1906-1980 (Book collections on Project MUSE., 2008)
In this companion to The Life of Johnny Reb, Bell Irvin Wiley explores the daily lives of the men in blue who fought to save the Union. With the help of many soldiers' letters and diaries, Wiley explains who these men were and why they fought, how they reacted to combat and the strain of prolonged conflict, and what they thought about the land and the people of Dixie. This fascinating social history reveals that while the Yanks and the Rebs fought for very different causes, the men on both sides were very much the same. ""This wonderfully interesting book is the finest memorial.